2007
DOI: 10.1371/journal.pone.0000573
|View full text |Cite
|
Sign up to set email alerts
|

Corticolimbic Expression of TRPC4 and TRPC5 Channels in the Rodent Brain

Abstract: The canonical transient receptor potential (TRPC) channels are a family of non-selective cation channels that are activated by increases in intracellular Ca2+ and Gq/phospholipase C-coupled receptors. We used quantitative real-time PCR, in situ hybridization, immunoblots and patch-clamp recording from several brain regions to examine the expression of the predominant TRPC channels in the rodent brain. Quantitative real-time PCR of the seven TRPC channels in the rodent brain revealed that TRPC4 and TRPC5 channe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
162
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(172 citation statements)
references
References 55 publications
10
162
0
Order By: Relevance
“…The localization of TRPC4 in the adult rat brain is consistent with previous in situ mRNA 1 . In this study we increased the resolution of the TRPC4 mRNA and protein to the cellular level and discovered selective co-localization of TRPC4 channels in subpopulations of TH-positive DA neurons.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The localization of TRPC4 in the adult rat brain is consistent with previous in situ mRNA 1 . In this study we increased the resolution of the TRPC4 mRNA and protein to the cellular level and discovered selective co-localization of TRPC4 channels in subpopulations of TH-positive DA neurons.…”
Section: Discussionsupporting
confidence: 89%
“…The TRPC family of nonselective channels are made up of seven members (TRPC1-7) and the TRPC4 channel is one of the two most abundant in the mammalian brain 1 . Our recent findings indicate that the TRPC4 channel is important for sociability in a rodent model of social interaction 3 .…”
mentioning
confidence: 99%
“…TRPC4 and TRPC5 are abundantly expressed in smooth muscle and central nervous system, but these expression patterns do not perfectly overlap (29,30). TRPC channels can function as both homo-and heterotetramers with a preference of heteromultimerization among members of the same TRPC subgroup, as well as TRPC1 with TRPC4/C5 (31-33).…”
Section: Discussionmentioning
confidence: 99%
“…While SKF96365 has been used extensively as a tool to define the functional roles of TRPC channels in various cell and tissue types (Bengtson et al, 2004;Fowler et al, 2007), previous studies reported notable overlapping effects on numerous channels in various organs (Merritt et al, 1990;Hong and Chang, 1994;Schwarz et al, 1994;Juvin et al, 2007;Liu et al, 2007). A high concentration of SKF96365 (30 M) partly affected low voltageactivated T-type calcium channels in Purkinje cells (Singh et al, 2010).…”
Section: Discussionmentioning
confidence: 99%